Bipartite fixed-time output containment control of heterogeneous linear multi-agent systems - Zihan Liu; Xisheng Zhan; Jie Wu; Huaicheng Yan (AIMS Mathematics, 2023)
This study researches the bipartite fixed-time output containment control problem of heterogeneous linear MASs with signed digraphs. The leaders' states can be estimated by a designed distributed bipartite compensator. Furthermore, each follower is allocated a time-varying coupling weight, an adaptive bipartite fixed-time protocol is raised which can estimate the leader's system matrix but also the leader's state. On the foundation of control protocols, followers' outputs are included by the convex hull constituted by leaders' outputs. In addition, by utilizing the Lyapunov function theory, some abundant speculative knowledges are deduced to guarantee adaptive bipartite fixed-time output containment of multi-agent systems. Finally, the feasibility of the anticipant theoretical results is verified by a set of simulation examples.